Using in situ simulation to improve care of the acutely ill patient by enhancing interprofessional working: a qualitative proof of concept study in primary care in England - Amy Halls; Mohan Kanagasundaram; Margaret Lau-Walker; Hilary Diack; Simon Bettles (BMJ Open)
Objective Acutely unwell patients in the primary care setting are uncommon, but their successful management requires involvement from staff (clinical and non-clinical) working as a cohesive team. Despite the advantages of interprofessional education being well documented, there is little research evidence of this within primary care. Enhancing interprofessional working could ultimately improve care of the acutely ill patient. This proof of concept study aimed to develop an in situ simulation of a medical emergency to use within primary care, and assess its acceptability and utility through participants’ reported experiences.Setting Three research-active General Practices in south east England. Nine staff members per practice consented to participate, representing clinical and non-clinical professions.Methods The intervention of an in situ simulation scenario of a cardiac arrest was developed by the research team. For the evaluation, staff participated in individual qualitative semistructured interviews following the in situ simulation: these focused on their experiences of participating, with particular attention on interdisciplinary training and potential future developments of the in situ simulation.Results The in situ simulation was appropriate for use within the participating General Practices. Qualitative thematic analysis of the interviews identified four themes: (1) apprehension and (un)willing participation, (2) reflection on the simulation design, (3) experiences of the scenario and (4) training.Conclusions This study suggests in situ simulation can be an acceptable approach for interdisciplinary team training within primary care, being well-received by practices and staff. This contributes to a fuller understanding of how in situ simulation can benefit both workforce and patients. Future research is needed to further refine the in situ simulation training session.